Unveiling freshwater fungi from the Hanjiang River Basin in South China: Introducing Neolindgomyces guttulatus sp. nov. (Lindgomycetaceae, Pleosporales) - Li, Hongze; Shu, Yongxin; Lin, Jingjun; Zhou, Yitong; Liu, Jiayu; Doilom, Mingkwan; Dong, Wei (Phytotaxa, 2026)
The Hanjiang River, the second largest river in Guangdong Province after the Pearl River basin, flows into the South China Sea via Shantou City. It serves as a good reservoir for studying the ecological niche evolution of freshwater fungi in South China. However, the relevant study remains largely poor. In this study, an interesting species in its sexual morph was collected from the downstream of the river. Morphological study and multi-locus phylogenetic analysis of a concatenated LSU, SSU, ITS, tef1-α, and rpb2 dataset demonstrated that this collection represented as an undescribed species, which is introduced here as a novel species, Neolindgomyces guttulatus. The new species is characterized by immersed, globose to subglobose ascomata, clavate, bitunicate asci, and cylindrical-fusiform, hyaline, 8–9-septate, minutely guttulate ascospores with narrow and rounded ends, and a prominent gelatinous sheath. This study reports the first freshwater record of Neolindgomyces species in China, which expands the known diversity of the genus.